1992
DOI: 10.1111/j.1748-1716.1992.tb09379.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide attenuates pressor but enhances natriuretic responses to angiotensin II in pregnant conscious goats

Abstract: This study was designed to examine the actions of ANP in acute, ANGII-mediated hypertension during pregnancy. Effects on blood pressure, blood volume, and renal Na and K excretion were evaluated in conscious goats (n = 6). ANP (2 micrograms min-1), ANGII (0.5 microgram min-1), or ANGII+ANP (doses the same as for each peptide alone) was infused intravenously for 60 min. The pressor response to ANGII was reduced in pregnant goats. This reduction was seen in systolic, but not in diastolic pressure. ANP decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This plasma volume expansion of pregnancy also occurs in animal models and is the result of net, continual renal sodium and fluid retention (1). Previous findings in our laboratory and others have indicated that in normal pregnancy the natriuretic response to atrial natriuretic peptide (ANP) is blunted, therefore promoting sodium retention and plasma volume expansion (7,12,15,16).ANP signals through the second messenger cGMP, and we have reported that PDE-5 activity and protein abundance in the inner medullary collecting duct are selectively increased in normal pregnancy (14). In addition, selective, intrarenal PDE-5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (10).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…This plasma volume expansion of pregnancy also occurs in animal models and is the result of net, continual renal sodium and fluid retention (1). Previous findings in our laboratory and others have indicated that in normal pregnancy the natriuretic response to atrial natriuretic peptide (ANP) is blunted, therefore promoting sodium retention and plasma volume expansion (7,12,15,16).ANP signals through the second messenger cGMP, and we have reported that PDE-5 activity and protein abundance in the inner medullary collecting duct are selectively increased in normal pregnancy (14). In addition, selective, intrarenal PDE-5 inhibition with sildenafil reverses the blunted response to infused ANP seen in normal pregnancy (10).…”
mentioning
confidence: 77%
“…These data suggest that the renal response to natriuretic stimuli that act via the adenylyl cyclase-cAMP pathway is preserved during pregnancy. This is in contrast to the guanylyl cyclasecGMP pathway as the natriuretic response to ANP is blunted during pregnancy (7,12,15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings in our laboratory and from others have indicated that in normal pregnancy the natriuretic response to atrial natriuretic peptide (ANP) and the pressure-natriuresis response are blunted, therefore promoting sodium retention and plasma volume expansion (6,17,18,22,23). Pressureinduced natriuresis is dependent on the renal tubular actions of nitric oxide (NO, 16).…”
mentioning
confidence: 99%
“…The gestational plasma volume expansion is characterized by renal Na + and fluid retention. During normal pregnancy, natriuresis in response to atrial natriuretic peptide is remarkably reduced in rats16 and goats 17,18. The upregulation of aquaporin 2, a water channel expressed in the renal collecting duct, and a reduction of the osmotic thresholds for the vasopressin secretion and the perception of thirst during gestation also result in increased water intake and retention 14,19,20.…”
mentioning
confidence: 99%